Three hours - Roslund, Anders, 1961-; Hellström, Börge, 1957-2017- (Quercus, 2019)
Stockholm, Sweden. Seventy-three refugees have been found dead, suffocated in a container at Varta harbour. Niamey, Niger. Ewert Grens arrives in a city he's never heard of, in search of a man he never thought he would see again. Piet Hoffmann has again got himself in too deep, infiltrating a West African trafficking ring. He thinks he has two weeks to extricate himself, but will learn that his life, and that of countless defenceless people, now hangs on his actions during three desperate hours.